Generalized Equations for Potential Water Savings from Rainwater Tanks in Adelaide under Different Climates - Paudel Upendra; Imteaz Monzur A. (MATEC Web of Conferences, 2016)
With ever-increasing water demand, authorities around the world are considering different options including water recycling and rainwater harvesting to minimize potable water demand. Among all the alternative options, rainwater harvesting system is the most feasible to minimize potable water demand, This paper presents development of generalised equations for the quantifications of potential water savings under different climatic conditions for an Australian city, Adelaide. An earlier developed daily water balance model, eTank, which can calculate potential water savings in three climatic conditions (dry, average and wet) was used for this purpose. Several relationship graphs of water savings were produced through model calculations for different input parameters, i.e. roof area, tank volume and rainwater demand for each climatic condition. From the produced graphs, three (one for each climatic condition) generalised equations were developed, where water savings were presented as a function of roof area, demand and tank volume. Results from the developed equations were compared with model calculated results under different conditions and it is found that results from the generalised equations are very close to the model calculated results. Such equations are expected to be very helpful for general end users and will encourage them for implementing rainwater harvesting with prior knowledge.